Pengaruh Kebijakan Dividen dan Kinerja Keuangan Terhadap Nilai Perusahaan Pada Perusahaan LQ-45 Tahun 2023-2024 - Tambunan, Rupianna (Media Akuntansi Perpajakan, 2025)
This study aims to analyze the effect of dividend policy and financial performance on firm value in companies listed on the LQ45 Index of the Indonesia Stock Exchange during the 2023–2024 period. This research employs a quantitative approach using secondary data obtained from financial statements and annual reports of the companies. The sample consists of 36 companies selected from a total population of 90 companies using purposive sampling based on specific criteria relevant to the research objectives. Firm value is measured using the Tobin’s Q ratio, dividend policy is measured using the Dividend Payout Ratio, and financial performance is measured using Return on Equity (ROE). Hypothesis testing is conducted using a panel data linear regression model with the assistance of E-Views version 12 software. The results of the study indicate that dividend policy has a positive and significant effect on firm value, as does financial performance, which also shows a positive and significant effect on firm value. These findings suggest that consistent dividend distribution policies and strong financial performance are important factors in enhancing investor perceptions of firm value in the capital market. This research provides implications for company management and investors in making strategic decisions related to financial and investment policies.